Review of flight dynamics and controller design for unstable approach during landing - Abdullah, Ermira Junita; Romli, Fairuz Izzuddin; Syed, Asif Uz Zaman (Aerospace Society Malaysia, 2024)
This paper provides the essential literature review of aircraft controller design for the crucial landing phase. Fundamental ideas, modeling strategies, controller design approaches and most current developments in establishing safe and stable landings are covered in this overview. The purpose of the insights shared here is to support ongoing improvements in aircraft safety and operational effectiveness during landing.